Disembodied diagnostic: Creative thesis - Untivero, Dorynna Zyneensky L. (Animo Repository, 2016)
This project is an exercise on literary appropriation and other similar conceptualist poetic techniques through a series of thirty poems where original text is combined and/or juxtaposed with medical text. The source texts used in the project were gathered from transcribed (anonymous) medical radiology case files. The collection was divided into six chapters namely: Chief Complaint, History, Vital Signs, Physical Exam, Differential Diagnosis, and Radiographic Diagnosis. All of which contain five poems each. This collection serves as an exploration of the relationship between this particular applied science and literature, alongside the following themes: the concept of authorship and originality in the poetic text, the literariness of a work, and authorship in the world of intertextuality and digital information. The choice of Radiology as appropriated text is anchored on the theories under the practice of Found Poetry, Conceptual Poetry, and similar Avant-Garde traditions. It can be suggested that Radiology works around the same system of intertextuality, wherein the scan result/ interpretation (source text/s to be used in the project), serves as a copy of an x-ray scan, which is also rightfully, a mere copy of the human body an echo of the current problematic of intertextuality in the field of literature. This poetry collection focuses on the parallelisms between the two fields to interrogate these timely concerns.